Academic Freedom and Exit Exams in Higher Education: A Systematic Review - Teshome, Samson Worku (International Journal of Education, Management, and Technology, 2025)
Exit exams in higher education have become a contentious issue, particularly regarding their impact on academic freedom. This systematic review examines the intersection of exit exams and academic freedom by synthesizing findings from 32 peer-reviewed articles published between 1994 and 2024. The review follows the PRISMA framework to ensure methodological rigor and transparency. Key themes emerging from the literature include the role of exit exams in shaping curricula, influencing teaching practices, and affecting student outcomes. While proponents argue that exit exams standardize educational quality and enhance employability, critics contend that they impose rigid structures that constrain academic freedom. The review identifies significant regional variations in the implementation and perception of exit exams, with studies from Ethiopia, Germany, India, and the United States offering diverse perspectives. Methodologically, the reviewed studies employed case studies, surveys, and mixed-methods approaches, highlighting varying levels of evidence quality. The narrative analysis reveals that while exit exams can drive accountability and quality assurance, they often create tensions between institutional autonomy and centralized control. This review underscores the need for balanced policies that align exit exams with broader educational goals without compromising academic freedom. Future research should explore longitudinal impacts and innovative assessment models that reconcile these competing priorities.